The Evaluation of Community Empowerment through Society Forest Schemes - Rendra Setyadiharja; Raja Dachroni; Suherry (JIP (Jurnal Ilmu Pemerintahan) : Kajian Ilmu Pemerintahan dan Politik Daerah, 2019)
The Community Empowerment Program in the Busung and Kuala Sempang Villages of the Bintan Regency is carried out through a community forestry scheme, with a Mangrove Ecotourism program, a Mangrove Nursery, and Planting Program, a Fish, Shrimp, and Mangrove Crab Program, and a Mangrove Product Management Program. But there are still symptoms of problems in the administration of the program. This study aims to evaluate community empowerment programs in coastal villages through the community forestry scheme in Bintan Regency. Using Dale's concept of Program Evaluation, this research resulted in a holistic and evaluative explanation of the village community empowerment program through the community forestry scheme established in Bintan Regency. The results of this research are formative evaluative recommendations for the government and other stakeholders both at the regional and national scale in terms of formulating policies related to village community empowerment programs that use forest natural resources in the future.